Understanding Dry Matter and Nitrogen Accumulation for High‐Yielding Film‐Mulched Maize. (1st March 2014) - Liu, Jianliang; Zhan, Ai; Bu, Lingduo; Zhu, Lin; Luo, Shasha; Chen, Xinping; Cui, Zhenling; Li, Shiqing; Lee Hill, Robert; Zhao, Ying
Abstract : Film mulching is a very common technique in agriculture worldwide, but few studies have focused on the dry matter (DM) and N accumulation of mulched crops. Understanding the grain yield (GY) associated with DM and N accumulation is essential for improving crop production. We conducted a 3‐yr field experiment with six N fertilizer rates (0, 100, 200, 250, 300, and 400 kg ha −1 ) in the semiarid climate of northwest China to determine the GY and DM and N accumulation of film‐mulched maize ( Zea mays L.). The results showed that relatively high GYs (13.1–15.1 Mg ha −1 ) were obtained using N fertilizer rates of 200 to 400 kg ha −1 in the 3 yr despite large year‐to‐year differences in rainfall. When the N rate was below 250 kg ha −1, the GY, DM, and N accumulation increased significantly as the N fertilizer rate increased. A linear‐plateau model best described the relationship between the GY and the DM and N accumulation during the pre‐silking stage and a linear model the relationship during the post‐silking stage. We conclude that optimizing N management to improve DM and N accumulation (especially post‐silking) is the key to ensuring a high yield of film‐mulched maize.